Des archipels en péril ? Les Maldives et les Kiribati face au changement climatique - Virginie Duvat; Alexandre Magnan (VertigO)
This paper proposes a systemic and dynamic approach of the vulnerability of territories to coastal risks. The approach is applied to two Small Island Developing States, the Maldives and Kiribati. The authors present the 'resources system” of such states and they discuss how the predictable impacts of climate change might affect their vulnerability. In addition, they expose the adaptive strategies developed by those island states as pioneers of adaptation, as they are on the first line of climate change impacts. It also shows that such countries raise major issues that are also relevant in other territorial contexts.